Comparative studies on the corrosion inhibition characteristics of three different triazine based Schiff’s bases, HMMT, DHMMT and MHMMT, for mild steel exposed in sulfuric acid - M. Prajila; P. Rugmini Ammal; Abraham Joseph (Egyptian Journal of Petroleum)
The inhibition behavior of three different triazine based Schiff’s bases, HMMT, DHMMT and MHMMT for mild steel corrosion in sulphuric acid has been investigated using weight loss, electrochemical studies, SEM, spectroscopic studies and basic computational studies. The inhibition efficiency increased with increase in inhibitor concentration but decreased with rise in temperature and acid concentration in the case of these three inhibitors. The order of inhibition efficiency expected from the values of band energy is in good agreement with the results obtained from weight loss and electrochemical studies. Polarization studies indicated the mixed type behavior of these inhibitors. Field emission scanning electron microscopic studies revealed that inhibitors protect the metal surface by the forming a protective film through adsorption of inhibitor molecules. Keywords: Mild steel, Corrosion inhibition, Schiff’s bases